Textual Equivalence of Cohesive Devices in Arabic-Indonesian Personal References - Mufidah, Shofiy Petrina; Masrukhi, Moh (LP2M IAIN Sultan Amai Gorontalo, 2024)
The textual equivalence between the source text (ST) and the target text (TT) is greatly influenced by cohesive device translation. This article aims to analyze textual equivalence in translating personal references from Arabic to Indonesian. This research is a qualitative descriptive study using Halliday and Hasan's (1976) theory of cohesion and Baker's (2018) theory of cohesiveness in textual equivalence. The data came from the narrative discourse of the saga genre of the book 'Wali Tanah Jawa' in the form of the Arabic text